2013
DOI: 10.1371/journal.pone.0056798
|View full text |Cite
|
Sign up to set email alerts
|

LegC3, an Effector Protein from Legionella pneumophila, Inhibits Homotypic Yeast Vacuole Fusion In Vivo and In Vitro

Abstract: During infection, the intracellular pathogenic bacterium Legionella pneumophila causes an extensive remodeling of host membrane trafficking pathways, both in the construction of a replication-competent vacuole comprised of ER-derived vesicles and plasma membrane components, and in the inhibition of normal phagosome:endosome/lysosome fusion pathways. Here, we identify the LegC3 secreted effector protein from L. pneumophila as able to inhibit a SNARE- and Rab GTPase-dependent membrane fusion pathway in vitro, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 92 publications
0
46
0
Order By: Relevance
“…The chlamydial T3SS substrate IncA harbors two SNARElike coiled-coil motifs (58) and inhibits membrane fusion mediated by endocytic, but not exocytic, SNARE complexes (59). Expression of the L. pneumophila effector LegC3 produces a vacuolar protein sorting defect in yeast (40) linked to the disruption of trans-SNARE complexes by coiled-coil domains within the effector (60). In contrast to L. pneumophila and Chlamydia spp.…”
Section: Discussionmentioning
confidence: 99%
“…The chlamydial T3SS substrate IncA harbors two SNARElike coiled-coil motifs (58) and inhibits membrane fusion mediated by endocytic, but not exocytic, SNARE complexes (59). Expression of the L. pneumophila effector LegC3 produces a vacuolar protein sorting defect in yeast (40) linked to the disruption of trans-SNARE complexes by coiled-coil domains within the effector (60). In contrast to L. pneumophila and Chlamydia spp.…”
Section: Discussionmentioning
confidence: 99%
“…The net result is that EEA1, which binds to PI(3)P, no longer associates with the endosome. Legionella also expresses LegC3, a protein with a ‘SNARE-like’ N-terminal domain that blocks homotypic vacuole fusion events in yeast (48). It is not difficult to imagine that Brucella likewise expresses proteins that inhibit membrane fusion in order to maintain its preferred replicative niche and evade destruction within lysosomes.…”
Section: Pathogens In Tight Vacuoles Restrict Membrane Fusionmentioning
confidence: 99%
“…Indeed, LegC3 was shown previously to inhibit SNARE-mediated homotypic fusion of yeast vacuoles in vitro, but a direct interaction between LegC3 and SNAREs was not observed (21). We found that all three LegC proteins selectively interact with the R-SNARE vesicle-associated membrane protein 4 (VAMP4), and furthermore, that the availability of VAMP4 is rate limiting for the intracellular proliferation of Legionella.…”
mentioning
confidence: 68%